2023
DOI: 10.1111/issj.12413
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the role of fiscal and monetary policy instruments on carbon emission in non‐linear framework: A case of emerging economy

Abstract: India is the second most populous country in the world and stood at seventh rank in a major climate risk index in 2019, which is a grave concern for the Indian government, policymakers and environmentalists. Therefore, the present study examines the role of fiscal policy and monetary policy instruments along with select macroeconomic variables on carbon emission in India over the period 1971–2019 in the non‐linear framework. The outcome of the study reveals that the impact of fiscal and monetary policy instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The results of the MTNARDL model for model 3 and 4 demonstrated that the impact of extreme large changes in FD varies from the impact of moderate and low changes, validating the long-term asymmetry. The strand of literature [ 35 , 51 , [93] , [94] , [95] ] also confirmed that FD exhibits an asymmetric impact in the long term. For robustness, the study has employed the WALD test to investigate the asymmetry between the extreme large and extreme small changes in FD in both the short- and long-run.…”
Section: Empirical Analysismentioning
confidence: 75%
See 2 more Smart Citations
“…The results of the MTNARDL model for model 3 and 4 demonstrated that the impact of extreme large changes in FD varies from the impact of moderate and low changes, validating the long-term asymmetry. The strand of literature [ 35 , 51 , [93] , [94] , [95] ] also confirmed that FD exhibits an asymmetric impact in the long term. For robustness, the study has employed the WALD test to investigate the asymmetry between the extreme large and extreme small changes in FD in both the short- and long-run.…”
Section: Empirical Analysismentioning
confidence: 75%
“…Numerous studies have shown that a number of macroeconomic factors, including energy use, urbanisation, trade openness, and financial development, have a significant impact on environmental deterioration [ 35 , [50] , [51] , [52] , [53] , [54] ]. This section has presented the previous related literature on the nexus between the fiscal deficit and CO 2 emissions, and the nexus between other covariates and CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While empirical studies contribute vital insights into the practical manifestations of these policies, this paper firmly anchors itself in the realm of economic theory. Notably, recent theoretical discussions, as exemplified by works like Mawejje & Odihambo (2022) and Sharma, Fatima, Alam & Bharadwaj (2023), emphasise the need for a robust theoretical framework to comprehend the intricate relationships between fiscal and monetary policies. Mawejje & Odihambo (2022) and delve into the theoretical nuances of fiscal dominance in a low-interest-rate environment, offering conceptual clarity on the challenges posed.…”
Section: Introductionmentioning
confidence: 99%
“…Mawejje & Odihambo (2022) and delve into the theoretical nuances of fiscal dominance in a low-interest-rate environment, offering conceptual clarity on the challenges posed. Sharma (2023) contributes to the ongoing theoretical discourse by exploring the nonlinear dynamics between fiscal and monetary policies. Thus, this 2 paper positions itself within the contemporary economic context, drawing on these theoretical advancements to deepen our understanding of the intricate theoretical dimensions of fiscal dominance and its implications for monetary policy transmission.…”
Section: Introductionmentioning
confidence: 99%